Differential fuel utilization in liver transplant recipients and its relationship with non‐alcoholic fatty liver disease. (24th February 2022) - Siddiqui, Mohammad S.; Patel, Samarth; Forsgren, Mikael; Bui, Anh T.; Shen, Steve; Syed, Taseen; Boyett, Sherry; Chen, Shanshan; Sanyal, Arun J.; Wolver, Susan; Kirkman, Danielle; Celi, Francesco S.; et al.
Abstract: Metabolic flexibility is the ability to match biofuel availability to utilization. Reduced metabolic flexibility, or lower fatty acid (FA) oxidation in the fasted state, is associated with obesity. The present study evaluated metabolic flexibility after liver transplantation (LT). Methods: Patients receiving LT for non‐alcoholic steatohepatitis (NASH) ( n  = 35) and non‐NASH ( n  = 10) were enrolled. NASH was chosen as these patients are at the highest risk of metabolic complications. Metabolic flexibility was measured using whole‐body calorimetry and expressed as respiratory quotient (RQ), which ranges from 0.7 (pure FA oxidation) to 1.0 is (carbohydrate oxidation). Results: The two cohorts were similar except for a higher prevalence of obesity and diabetes in the NASH cohort. Post‐prandially, RQ increased in both cohorts (i.e. greater carbohydrate utilization) but peak RQ and time at peak RQ was higher in the NASH cohort. Fasting RQ in NASH was significantly higher (0.845 vs. 0.772, p  < .001), indicative of impaired FA utilization. In subgroup analysis of the NASH cohort, body mass index but not liver fat content (MRI‐PDFF) was an independent predictor of fasting RQ. In NASH, fasting RQ inversely correlated with fat‐free muscle volume and directly with visceral adipose tissue. Conclusion: Reduced metabolic flexibility in patients transplanted for NASH cirrhosis may precede the development of non‐alcoholic fatty liver disease after LT.